Relationship between level of computer game addiction and behavioral problems among children - Sallayıcı, Zeynep; Yöndem, Zeynep Deniz (Journal of Dependence, 2020)
Objective: Purpose of this research is to analyze the relationship between level of computer game addiction and behavioural problems, competence levels in school and non-school activities among children.Method: Associative survey model is used in the research. Participants of the research consist of 154 children receiving elementary education in 3rd and 4th class levels. “Computer Game Addiction Scale for Children” and “Behaviour Assessment Scale for 6-18 Years old Children and Young Persons” are used for collecting research data.Results: Among children participating the research, 56,5% (87 children) are at 3rd class level, 43,5% (67 children) are at 4th class level and 52,6% (81 children) of them are girl, 47,4% (73 children) are boy and the total number of children is 154. A positive correlation is found between computer game addiction level and external behavioural problems, aggression, social problems, cautiousness problems, thought problems; however negative correlation was found between the computer game addiction level and children’s school competence.Conclusion: While there is a meaningful relationship between computer game addiction and external behavior problems, there is no meaningful relationship with internal behavior problems.
Keywords: Computer game addiction; behavioural problems; children